A concretização do reconhecimento extrajudicial da paternidade socioafetiva e multiparentalidade: análise do Provimento nº 63 do Conselho Nacional de Justiça - Cabral Filho, Alcides Lourenço (2021)
It will be shown that the realization of the recognition of paternity and mutual parenthood through extrajudicial means, approved and regulated by Provision 63 of the National Council of Justice, subsequently amended by Provision 83 of the same body, allowed an agile and dynamic way to solve the issue of recognition of paternity from another origin, without having to go through the courts. The possession of the status of child is an institute that was not expressly accepted in our Civil Code, both the one of 1916 and the current one, but it constitutes the external face of paternity or socio-affective maternity, as well as multiparentality, to provide the formation of a plural family context, no longer based only on marriage, but admitting its formation in view of new forms of family composition, such as stable union, as well as those formed by homosexual couples, the single-parent family. Affectivity emerges as an essential subjective element of paternity to the extent that not only the biological bond allows the establishment of kinship, but also admits its consolidation under the civil form based on another origin, as provided in the current Civil Code. Provision 63 of the National Inspector of Justice laid the foundations for the recognition of social-affective paternity or maternity, as well as multi-parenthood, to be carried out extrajudicially, directly at the Civil Registry Office, upon proof of the bonds of affection and exteriorization of this relationship in the social environment, since until then judicial pronouncement was required for such a measure. We analyze the historical and philosophical aspects of paternity and filiation, the family power and its exercise, with special emphasis on the nature of social-affective filiation and multiparenthood, with its own chapter on the recognition of paternity and on the normative attributions of the National Council of Justice, to finally proceed to an in-depth analysis of Prov. No. 63 and its repercussions in the family contex